2012
DOI: 10.1149/2.042211jes
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Induced Hysteresis in CuCo-Doped Rare Earth Vanadates SOFC Anodes

Abstract: The physical and electrochemical properties of strontium substituted cerium vandates in which a portion of the cerium cations have been substituted with transition metals (Ce 0.8 Sr 0.1 Cu 0.05 TM 0.05 VO 4−0.5x , TM = Ni or Co) were investigated and their suitability for use in solid oxide fuel cell (SOFC) anodes was assessed. Upon reduction at elevated temperature, Cu and Co or Cu and Ni were exsolved from the electronically conductive Ce 1−x Sr x VO 4 lattice to produce Cu-Ni and Cu-Co catalytic nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…This type of catalyst is based on catalytically active metal particles being prepared by reduction of perovskite-type oxides, which contain reducible transition metals. Upon reduction, the transition metal is exsolved from the perovskite lattice and forms metallic precipitates on the oxide surface 3,4,7,8,[13][14][15][16][17][18][19][20] . In contrast to deposition of a catalytically active metal on top of an oxide, this approach yields nanoparticles that are socketed in the oxide and thus much less prone to particle growth at elevated temperatures 3,21 .…”
mentioning
confidence: 99%
“…This type of catalyst is based on catalytically active metal particles being prepared by reduction of perovskite-type oxides, which contain reducible transition metals. Upon reduction, the transition metal is exsolved from the perovskite lattice and forms metallic precipitates on the oxide surface 3,4,7,8,[13][14][15][16][17][18][19][20] . In contrast to deposition of a catalytically active metal on top of an oxide, this approach yields nanoparticles that are socketed in the oxide and thus much less prone to particle growth at elevated temperatures 3,21 .…”
mentioning
confidence: 99%
“…Alternatively, an emerging concept is to grow the nanoparticles in situ, by reduction or during catalytic reaction, directly from the (porous) oxide backbone support itself [4][5][6]. Perovskites (nominal composition ABO3 with A and B being a large and small cation, respectively) can incorporate catalytically highly active elements as cations on the B-site of the perovskite lattice (e.g., Ni [4,7], Fe [4,8], Co [9], Cu [4,9], Pt [10], Pd [10,11]). Upon exposure to reducing conditions, these elements can be partly exsolved as nanoparticles, thus opening the possibility of in situ growth of active catalysts [12], see sketch in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods is to incorporate the metal as a dopant into the material sublattice during the synthesis in air, which can be then exsolved at the grain-surface in the metallic form of catalytically active metal nanoparticles under reducing conditions. It was recently shown that electro-catalytic nanoparticles can be produced in oxide anodes by incorporating Ni, Co, Cu, Fe, Pd into perovskite oxide [5,6]. These catalytically active nanoparticles can be incorporated back into the substrate to form a homogeneous ceramic where the exsolved specie is again a dopant into the sublattice [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%